2013
DOI: 10.1088/1054-660x/23/11/115102
|View full text |Cite
|
Sign up to set email alerts
|

AQ-switched thulium-doped fiber laser with a graphene thin film based saturable absorber

Abstract: We demonstrate a simple, compact and low cost Q-switched thulium-doped fiber laser (TDFL) operating at 1844.1 nm by exploiting a graphene based saturable absorber (SA) in conjunction with 1552 nm pumping. The SA is fabricated by sandwiching the graphene thin film between two fiber connectors. The thin film was produced by mixing graphene flakes, synthesized by an electrochemical exfoliation process, with polyethylene oxide (PEO) solution. The TDFL generates a stable pulse train with 6.73 kHz repetition rate, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…The performance of our fabricated graphene-PVA SA in 2,000 nm region is better than the result reported by Saidin et al [13], [14] and Ahmad et al [15]. We strongly believed that this maybe contributed by our meticulous preparation of the graphene-PVA film using electrochemical exfoliation technique.…”
Section: Figure 3 Cavity Ring Measurement Setupcontrasting
confidence: 53%
See 2 more Smart Citations
“…The performance of our fabricated graphene-PVA SA in 2,000 nm region is better than the result reported by Saidin et al [13], [14] and Ahmad et al [15]. We strongly believed that this maybe contributed by our meticulous preparation of the graphene-PVA film using electrochemical exfoliation technique.…”
Section: Figure 3 Cavity Ring Measurement Setupcontrasting
confidence: 53%
“…Ahmad et al [15] employed optical deposition approach of graphene oxide particles and they reported a Qswitched pulse with maximum repetition rate of 16 kHz, shortest pulse width of 9.8 µs and maximum pulse Indonesian J Elec Eng & Comp Sci ISSN: 2502-4752  energy of 18.8 nJ. Saidin et al [13], [14], demonstrated a graphene-PEO based passive saturable absorber with repetition rate of 7.5 kHz, 19.7 µs pulse width and maximum pulse energy of 66.6 nJ. In this work, we produce higher range of repetition rate, shortest pulse width compared to the work proposed by Saidin et al [13], [14] and Ahmad et al [15], and higher average output power than Ahmad et al [14].…”
Section: Figure 3 Cavity Ring Measurement Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…When a voltage is applied in a conductive solution for the graphite electrodes, the graphite electrodes can corrode and produce the solvent-functioning graphite nanosheets (see Figure 11) [147]. The use of electrochemical exfoliation of graphite anode to prepare graphene was first reported by [126] using a mixed solution containing ionic liquid and water as the electrolyte.…”
Section: Electrochemical Exfoliation Of Graphitementioning
confidence: 99%
“…. They can be realized using a Thulium‐doped fiber (TDF) as a gain medium , which has a broad emission in the wavelength range of 1650 and 2100 nm due to energy transition of 3 F 4 → 3 H 6 . A significant interest has also emerged on TDF pulsed lasers.…”
Section: Introductionmentioning
confidence: 99%